Biosorption of Cu II and Cd II Heavy Metals from Aqueous Solutions by Paprika Waste - Kalak, Tomasz; Dudczak, Joanna; Szychowiak, Elwira; Cierpiszewski, Ryszard (Studia Oeconomica Posnaniensia, 2017)
In this study, the adsorption conditions of Cu(II) and Cd(II) metal ions onto dried paprika residues have been studied. Paprika waste is generated in the food industry and it can be used for removing copper Cu(II) and cadmium Cd(II) from wastewater. Paprika is usually consumed as a fresh fruit or dried and used as ground and natural flavouring in the food industry, but also as a colouring agent for many food products, such as spicy culinary, cheese food coatings, meat products, popcorn oil etc. It is also used in the pharmaceutical and cosmetic industries. Spice pepper is added to dried soups, cheese, chips and spice mixtures. Paprika is a source of biologically active compounds, such as flavonoids, phenols, carotenoids, capsaicinoids and vitamins. Its fruits contain resins, pentosans, cellulose, protein, pungent principles, colouring pigments, mineral elements and small amounts of volatile oil. Seeds include fixed non-volatile oil, which consists of triglycerides ( 60%), mainly linoleic acid and other unsaturated fatty acids. All the ingredients exhibit various benefits to human health, antioxidant capacity and other biological activities, but also sorption properties in relation to heavy metal ions. In this research the adsorption of metal ions like Cu(II) and Cd(II) from aqueous solutions at different pH values 2-5 has been investigated. The tests were conducted to study the effects of the mass of biosorbent, various metal ion concentration, pH level, contact time on adsorption isotherms of the metals and a maximum loading capacity. The results showed that the copper and cadmium ions were significantly bound by paprika waste, which was also confirmed by FT-IR.